Hematological and biochemical indicators of lambs’ blood after the use of chemotherapeutic agents for spontaneous eimeriosis - Filipenko, O. V.; Soroka, N. M. (Regulatory Mechanisms in Biosystems, 2023)
Eimeria infection is one of the protozoal diseases of animals caused by various species of Eimeria and causes reduced productivity and raised mortality in ruminants, especially in young ones. To study the effect of anti-emeriosis drugs on the morphological and biochemical parameters of lambs’ blood infected with Eimeria, 3 groups of Romanov breed animals, two months old, affected by the Eimeria pathogen were formed. The first group of animals was treated with a drug containing the active ingredient decoquinate; the second group of animals with a drug containing the active ingredient toltrazuril; the third group of lambs were given a combined drug containing 80 mg of norsulfazole, 70 mg of sulgin, 30 mg of trimethoprim, 45 mg of oxytetracycline hydrochloride and 25 mg of tylosin tartrate per 1 g); the fourth group of lambs was the control group, the animals were free from the Eimeria pathogen and were kept separately. The blood of the animals was analysed on days 7 and 14 of treatment. In the blood of the experimental lambs, an increase in the number of red blood cells, neutrophils, lymphocytes, and monocytes was noted. There was also a decrease in the total number of leukocytes, eosinophils, young and segmented neutrophils. According to the results of the treatment, there was an increase in the content of total, albumin, hemoglobin and glucose, as well as the activity of gamma-glutamate transferase. At the same time, there was a decrease in the content of globulins and the activity of aspartate aminotransferase and alanine aminotransferase compared to the biochemical parameters of healthy lamb blood serum of the control group. According to treatment results, the restoration of sick lambs’ blood parameters to those of healthy animals was noted; however, the most stable effect was using the combined drug.